Entrepreneurship in an Amateur World: The Gaelic Athletic Association in Ireland. Issue 7 (24th May 2018) - Cronin, Mike
Abstract: The Gaelic Athletic Association (GAA) is unusual in the world of contemporary sport. While at the organizational level it is wholly corporate and follows standard global models of maximizing revenue from media deals and sponsorship, the players remain entirely amateur. As a result, rather than profits being removed from the organization in terms of dividends, the income is recycled through the grassroots of the organization so that local communities benefit. This is at odds with the two other major sports in Ireland, soccer and rugby, which both spend a large percentage of their revenue on player contracts and therefore only recycle comparatively small amounts of money to their grass roots. Historically, the GAA did not embrace entrepreneurship due to the nature of the general national economy, a lack of modernization and the drain of emigration from the island. It was only until the economic boom of the 1990s that the GAA began to innovate entrepreneurially, and the success of this strategy is evidenced by a healthy profit that is underpinned by a commitment to amateurism.